Reviewing the Factors Influencing New Policy Petrochemical Plants Over the Last Decade (Case Study: Petrochemical Special Economic Zone of Mahshahr) - Maryam, Salamatahvazi (International Review of Management and Marketing, 2017)
Petrochemical industry is an important source for meeting the needs of country’s domestic industries and it is an important source of exchange. We can reduce the raw material imports and increase the exporting of production with high added value and we save the exchange by the establishment of the petrochemical complexes. This study is a retrospective research and the policy making for the establishment of petrochemical plants has been examined. The objective of the study is to criticize and review the factors affecting the policy-making for the establishment of the new petrochemical plants over the past decade. The method of study is descriptive-survey. The data were collected by reviewing the documents and resources. The study population consisted of all highly qualified staff, experts and specialists who work in Petrochemical Special Economic Zone of Mahshahr. The researcher- made questionnaire with high and proper reliability and validity was randomly distributed among samples. The Data were analyzed. The compiled results using AMOS and SPSS software revealed that three aspects of rules and regulations, market and structure had significant effect on the policy-making for the establishment of economic zone of Mahshahr. Keywords: Review and Analysis, Policy, Petrochemical industry. JEL Classification: O2